2007
DOI: 10.3177/jnsv.53.457
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Biotin in Growing Ovarian Follicles and Embryonic Development in Domestic Fowl

Abstract: Summary It is well known that biotin deficiency causes morphological anomalies in hatchlings of fowl. An abundance of biotin in the yolk, therefore, is greatly required for maintaining reproductive functions. Although there is growing evidence for the molecular significance of the vitamin in the processes of the reproductive system in mammals, little is known about its use and roles in fowl's yolk. This review focuses on studies on the roles of biotin in the ovarian follicles and embryos of domestic fowl. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…However, pullets of control one was delayed in reaching to age of sexual maturity (154.05 day). The results were agreed with those reported by Taniguchi and Watanabe (2007) they demonstrated that the age at sexual maturity significant affected with biotin supplementation levels scenes it promote the early growing ovarian follicles, incorporated into the follicles, particularly in a large amount immediately before ovulation. It incorporated from the early stage to the growth stage of ovarian follicles that was stored in the protein-binding form and became available again immediately before the ovulation.…”
Section: Age At Sexual Maturity Egg Production Rate Egg Weight and supporting
confidence: 92%
“…However, pullets of control one was delayed in reaching to age of sexual maturity (154.05 day). The results were agreed with those reported by Taniguchi and Watanabe (2007) they demonstrated that the age at sexual maturity significant affected with biotin supplementation levels scenes it promote the early growing ovarian follicles, incorporated into the follicles, particularly in a large amount immediately before ovulation. It incorporated from the early stage to the growth stage of ovarian follicles that was stored in the protein-binding form and became available again immediately before the ovulation.…”
Section: Age At Sexual Maturity Egg Production Rate Egg Weight and supporting
confidence: 92%
“…From these findings, it is suggested that biotin may be associated with the expression and production of these carboxylases and organic acids may be concerned with retardation of palatal formation in vivo. Also, the presence of ACC was only slight, even in biotin-supplemented embryos as well as in the fertilized eggs of hens (Taniguchi & Watanabe 2007). Thus, fatty acid synthesis may not work in the embryos of fowl or mammals.…”
Section: Discussionmentioning
confidence: 93%
“…The method allows application of the biotinstreptavidin detection system to perform Western blot work with cells from zebrafish (Danio rerio) embryos and it will be applicable to tissues from kidney, liver and mammary gland, which are rich in endogenous biotin or biotinylated proteins (Dakshinamurti and Mistry, 1963;Moss and Lane, 2006;Taniguchi and Watanabe, 2007;Wood and Barden, 1977).…”
Section: Resultsmentioning
confidence: 99%